Penguatan Manajemen Pemasaran dalam Meningkatkan Daya Saing Produk Unggulan di Desa Muara Telake Kabupaten Paser - Fitriyana Fitriyana; Andi Noor Asikin; Indah Sriwahyuni; Yulianti Yulianti (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2025)
The wives of fishermen in Muara Telake Village, Paser Regency, have significant potential to develop local specialty products. However, their competitiveness remains low due to weak marketing management, limited business knowledge, and uninnovative packaging. This Community Service (PKM) program was carried out with the aim of strengthening the marketing management of local superior products in Muara Telake Village, Paser Regency. The main problems faced by the partners were weak marketing strategies, limited knowledge of business management, and a lack of innovation in product packaging, which had an impact on low competitiveness in both local and regional markets. The implementation method used a participatory approach through several stages, including needs analysis, marketing management training, assistance in digital promotion management, and training in product design and packaging that meet market standards. The results of the program indicate an improvement in the partners understanding of marketing strategy planning, their ability to manage digital-based promotion, and their skills in developing more attractive and consumer-oriented packaging. This capacity strengthening is expected to enhance the competitiveness of local superior products, expand market reach, and contribute to improving the income of fishing communities. Therefore, this PKM not only provides practical solutions to marketing problems, but also supports sustainable economic empowerment for coastal communities.